The acute effect of cardiac pacing mode on endothelial vasodilation: Prospective, double-blind, cross-over, comparative clinical study - FAK, ALİ SERDAR; ÖZBEN SADIÇ, BESTE (BLACKWELL PUBLISHING, 2008)
Background: Compared to atrioventricular sequential pacing, ventricular demand pacing is known to have somewhat more deleterious hemodynamic effects, which probably arise from increased sympathetic tonus and inappropriate baroreceptor activation. Endothelial function is affected by various local and systemic factors including baroreceptor activity. The aim of this study was to explore whether cardiac pacing would have any effect on endothelial functions. Methods: Twelve patients (six male, mean age: 75 +/- 9 years) with previously implanted DDD or VDD cardiac pacemakers were included. All patients had stable atrial rhythms during the study. Patients were randomized to either atrial-based pacing mode (VDD or DDD) or ventricular demand pacing mode (VVI) first, and then cross-over was performed with the other pacing mode. Endothelial function was assessed by brachial artery ultrasonography. Basal diameter of the brachial artery, and both flow-mediated dilation (FMD) and endothelium-independent vasodilation with nitroglycerin were measured 1 hour after each pacing mode. Results: Compared to atrial-based pacing mode, ventricular demand pacing was associated with a significantly worse FMD both as absolute and percentage values (0.17 +/- 0.09 mm vs 0.28 +/- 0.11 mm, P = 0.015 and 4.84 +/- 2.37 % vs 7.00 +/- 2.88 %, P = 0.028, respectively). However, there was no significant difference in nitroglycerin-mediated vasodilation values between the two pacing sessions. Conclusions: Acute ventricular demand pacing (VVI pacing) is clearly associated with attenuation of FMD in patients with atrial-based pacing systems. The attenuation of endothelial vasodilation might have a role in hemodynamic and clinical deterioration in patients with VVI pacemakers.
Keywords: cardiac pacemakers; pacing mode; endothelial function; FLOW-MEDIATED VASODILATION; PACEMAKER SYNDROME; HEMODYNAMIC CONSEQUENCES; EXERCISE PERFORMANCE; VENTRICULAR DEMAND; ATRIAL; DYSFUNCTION; DISEASE; HYPOTENSION; HUMANS